2021
DOI: 10.1111/issj.12267
|View full text |Cite
|
Sign up to set email alerts
|

Addressing work‐life balance challenges of working women during COVID‐19 in Bangladesh

Abstract: Working women face various challenges regarding work‐family balance due to societal, cultural, family, and gender norms. These challenges have become more difficult since the emergence of COVID‐19 worldwide. This qualitative research addresses work‐family issues of working women in the distinct Bangladeshi socio‐cultural context. Guided by a thematic analysis, this study explores various driving forces and challenges faced by working women, and strategies adopted by women to manage work‐family obligations. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
1
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(100 citation statements)
references
References 26 publications
4
72
1
7
Order By: Relevance
“…In addition, the COVID-19 pandemic has increased the stress of working mothers. Previous study has shown that working mothers have an increased role in preventing and protecting their families from COVID-19 [26]. Most of the participants in this study were working mothers and some could not take 2 weeks off for fear of being fired from their job.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, the COVID-19 pandemic has increased the stress of working mothers. Previous study has shown that working mothers have an increased role in preventing and protecting their families from COVID-19 [26]. Most of the participants in this study were working mothers and some could not take 2 weeks off for fear of being fired from their job.…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies reported the negative impact of the pandemic on faculty research activity, especially for women overseeing domestic and childcare activities. 30,32-35…”
Section: Discussionmentioning
confidence: 99%
“…Work-life balance is also about job flexibility, which determines the capacity of employees to define where, when and how they work. It includes elements such as the work program, workplace environment, reward and incentive structure, workloads and policies related to leaves (Uddin, 2021). Work-life balance is also about how to create a healthy and supportive work environment that improves employee performance (Wolor et al, 2020).…”
Section: Work-life Balance and Related Studies In The Pandemic Periodmentioning
confidence: 99%
“…It is noted that factors such as colleagues, managers, corporate support, and the workplace environment affect the work-life balance during the pandemic. It highlights work flexibility and home/telework as the main drivers of work-life balance in the pandemic (Uddin, 2021).…”
Section: Work-life Balance and Related Studies In The Pandemic Periodmentioning
confidence: 99%